PENGARUH KONFLIK PERAN DAN STRES KERJA TERHADAP KINERJA MELALUI WORK LIFE BALANCE SEBAGAI VARIABEL MEDIASI PADA KARYAWAN PT. BRINGIN KARYA SEJAHTERA - Dita Putri Karunia, (2023)
This thesis research is to determine the effect of the performance of employees such as construction industry companies who experience problems in doing work that should be mostly done outside the home. This research is a quantitative study to determine the effect of role conflict and work stress on performance through work life balance as a mediating variable. The data collection method used in this study is using a sampling technique, namely probability sampling with the sample used, namely PT Bringin Karya Sejahtera with a total of 222 employees. In testing the hypothesis that was carried out in this study using the determinant coefficient test (R2), partial test (T test). The Role Conflict Variable on Performance has a t value of 0.930 t table 1.65950 and the resulting p value is 0.000 0.05. the variable of work stress on performance is t count 0.713 t table 1.65950 and a p value of 0.000 0.05. Work life balance is capable of being a mediating variable for the effect of role conflict on performance, this can be seen from the t-count value of 0.101 t-table 1.65950 and has a p-value of 0.050 0.05. Work life balance is capable of being a mediating variable for the effect of work stress on performance, this can be seen from the t-count value of 0.237 t-table 1.65950 and has a p-value of 0.000 0.05. The work life balance variable does not affect performance by t count -0.055 t table 1.65950 and has a p value of 0.000 0.05. The results obtained from this study are (1) Role conflict has an influence on the performance of employees of PT Bringin Karya Sejahtera (2) Work stress has an influence on the performance of employees of PT Bringin Karya Sejahtera. (3) Work life balance is not able to be a moderating variable for the effect of role conflict on performance. (4) Work life balance is not able to be a moderating variable for the effect of work stress on performance. (5) Work Life Balance has an influence on the performance of employees of PT Bringin Karya Sejahtera. Keywords: Role Conflict; Work Stress; Performance ; Work Life Balance